Engineering geological problems of shear and fault zones in Nepal Himalaya (Journal of Nepal Geological Society, 2006)
Shear zones and faults pose serious engineering geological problems to the development of infrastructures. The problems are related to the contrasting properties of such zones which contain a weak matrix and strong rock fragments. Shear zones and faults are also frequently affected by groundwater.In this paper an attempt has been made to classify the shear or fault zones from an engineering geological point of view. The geotechnically problematic brittle shear or fault zones are generally sheared, shattered, powdered, or folded. They contain lenticular to angular fragments and randomly orientated rock clasts supported by a soft and weak matrix. They are further divided into clayey and blocky types. Some problems induced by such shear or fault zones in various hydropower and road projects of Nepal are also discussed.